Mindfully Green, Psychologically Keen: The Role of Green Mindfulness, Human Capital, and Adaptive Ability in Employee Green Performance - Rima Rahmayanti; Mariah Rabiatul Qibtiyah; Darwis Agustriyana (Universitas Islam Nahdlatul Ulama Jepara, 2026)
Objective: Climate change and sustainability demands have encouraged green hotels to strengthen human resource roles in supporting environmental initiatives. This study examines the effect of green mindfulness on employee green performance through the mediating roles of green human capital and green adaptive ability, as well as the moderating role of green psychological climate. Research Design & Methods: This study applied a quantitative method through a survey involving 225 employees from three- to five-star green hotels located in Bandung and Jakarta. The collected data were subsequently analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Findings: The results reveal that green mindfulness positively influences employee green performance both directly and indirectly through the mediating roles of green human capital and green adaptive ability. In addition, green psychological climate strengthens the relationships between green mindfulness and the three related green outcomes. Implications & Recommendations: These findings imply that green mindfulness functions not only at the individual level but also through the influence of the organizational climate. Therefore, hotels should embed green mindfulness into HR practices (e.g., training, performance management) while simultaneously fostering a supportive green psychological climate to maximize employee green performance. Contribution & Value Added: This study contributes to the existing literature by broadening the Green Human Resource Management (GHRM) framework through the incorporation of the Ability–Motivation–Opportunity (AMO) theory. The findings demonstrate the role of green mindfulness as a foundational psychological resource that activates green competencies and adaptive capacity in organizations.